A Global Assessment of Dissolved Organic Carbon in Precipitation. Issue 22 (27th November 2017) - Safieddine, Sarah A.; Heald, Colette L.
Abstract: Precipitation is the largest physical removal pathway of atmospheric reactive organic carbon in the form of dissolved organic carbon (DOC). We present the first global DOC distribution simulated with a global model. A total of 85 and 188 Tg C yr −1 are deposited to the ocean and the land, respectively, with DOC ranging between 0.1 and 10 mg C L −1 in this GEOS‐Chem simulation. We compare the 2010 simulated DOC to a 30 year synthesis of measurements. Despite limited measurements and imperfect temporal matching, the model is able to reproduce much of the spatial variability of DOC ( r  = 0.63), with a low bias of 35%. We present the global average carbon oxidation state ( OS c ¯ ) as a simple metric for describing the chemical composition. In the atmosphere, − 1.8 ≤ OS c ¯ ≤ − 0.6, and the increase in solubility upon oxidation leads to a global increase in OS c ¯ in precipitation with − 0.6 ≤ OS c ¯ DOC ≤ 0 . Key Points: We show the first simulated global dissolved organic carbon (DOC) distribution The model captures the measured DOC concentrations with r  = 0.63 and a bias of 35% despite imperfect temporal matching The global average carbon oxidation state ( OS c ¯ ) is shown for both atmospheric and dissolved organic carbon as a metric to describe chemical composition